Fiscal Policy Shocks and Private Consumption in Nigeria: Blanchard-Perotti (2002) Approach - Olasunkanmi, OSENI Isiaq (Journal of Economics and Behavioral Studies, 2015)
This paper examines the effects of fiscal policy shocks on private consumption in Nigeria. Albeit, there is a considerable number of works examining the effects of fiscal policy shocks on private consumption globally but in Nigeria, no study has used the structural VAR approach by Blanchard and Perotti (2002) as used in this paper. This approach relies on institutional information about the tax and transfer systems and the timing of tax collection to identify the automatic response of taxes and spending to private consumption as well as to infer fiscal shocks. The key result of this paper is that positive government spending shocks in Nigeria have an instantaneous negative effect on private consumption. The effect becomes significant in the period following the shock. Also, positive tax shocks have a negative effect on private consumption in the period of a shock and the effect becomes statistically insignificant afterwards. On this premises, one-off changes in government spending and taxes in Nigeria are long-lived and short-lived respectively. Thus, the government expenditure changes can be used to support private consumption in the long-run while that of taxes can only be used to support private consumption for a short period.